2022
DOI: 10.3390/ani12131631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Femoral Head and Neck Osteotomy on Canines’ Functional Pelvic Position and Locomotion

Abstract: The long-term effect of femoral head and neck osteotomy (FHO) on the locomotory system of dogs was evaluated. The study comprised an owner questionnaire and an orthopaedic examination, anatomical measurements, and pressure-sensitive walkway analysis for dogs. Linear mixed effect models were used for statistical analysis. Ten dogs with a median of 2.5 years since their unilateral FHO were included. According to the questionnaire results, nine dogs had returned to a normal physical activity level. Muscle atrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…However, decreased range of motion of the hip and muscle atrophy were detected, which did not interfere with normal activity. A study in 10 domestic dogs 6 months after FHO also observed muscle atrophy and decreased coxofemoral extension, which did not interfere with peak pressure and hindlimb stance and swing time at trotting evaluation over a pressure‐sensitive walkway 13 . Postoperative physical therapy is an option to increase limb function, but was not acceptable for a porcupine.…”
Section: Discussionmentioning
confidence: 99%
“…However, decreased range of motion of the hip and muscle atrophy were detected, which did not interfere with normal activity. A study in 10 domestic dogs 6 months after FHO also observed muscle atrophy and decreased coxofemoral extension, which did not interfere with peak pressure and hindlimb stance and swing time at trotting evaluation over a pressure‐sensitive walkway 13 . Postoperative physical therapy is an option to increase limb function, but was not acceptable for a porcupine.…”
Section: Discussionmentioning
confidence: 99%
“…Nun wird eine schräge Osteotomie angelegt, die von der Fossa trochanterica nach distal reicht. Ob die Osteotomie den Trochanter minor beinhalten sollte, wird unterschiedlich bewertet 54 , 55 . Eine klare Studienlage, inwiefern die Resektion des Trochanter minor das funktionelle Ergebnis beeinflusst, existiert nicht.…”
Section: Chirurgisches Managementunclassified
“…Jest to zabieg paliatywny, po którym dochodzi do powstania elastycznego połączenia łącznotkankowego pomiędzy kością udową i miednicą. Jakość i funk-cjonalność takiego połączenia zależą od staranności, z jaką zostanie przeprowadzony zabieg, a następnie rehabilitacja pooperacyjna (2,3).…”
Section: Praca Oryginalnaunclassified